Sugar Crisis: Status of Financial Income of Selected Bakery Shops in Brgy. Sauyo, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the status of the financial income of selected bakeryshops in terms of strategy or method, bread production demand, capital, and profit. Theshortage was caused by traders allegedly hoarding supply to rake in profits and importingsugar from other countries not exceeding 150,000 metric tons (MT).From the results of this study, it is clear that the most common strategy used by businessowners is adjusting ingredients used in baking, and bread production demand, capital, andprofit have been greatly impacted by the crisis. Based on the results, business ownersstrongly agreed on cutting off the use of sugar in baking pastries; this led us to conclude thatbusiness owners would shift their products. Based on the results, respondents would increasetheir investments in capital due to the decrease in the supply of sugar and would base thesalaries of their employees on the profit made by the shop.This study recommended that business owners should practically choose raw and processedingredients they buy in groceries or markets, balance the ingredients they use in baking inorder to maintain the richness of their products and remain able to satisfy the wants of theircustomers efficiently, and innovatively develop other products that can further help otherbusiness owners increase the success rate of their new product on the market. Lastly, werecommend business owners increase the visibility of their shops so that customers can easilybuy their products and to increase public awareness.
Keywords: Business